Adsorption, mobility, biotic and abiotic metabolism and degradation of pesticide exianliumi in three types of farmland. (September 2020) - Wang, Xin Qiang; Liu, Jintong; Zhang, Nan; Yang, Hong
Abstract: Exianliumi is a newly developed pesticide for controlling diseases caused by microbes or meloidogynes during plant vegetable and reproductive stages. To date, little is known about the environmental behavior and fate of its residues in soil. To explore its potential environmental risks to crop production and food safety, three typical Chinese agricultural soils were examined by analyzing adsorption, mobility leaching, and degraded metabolites of exianliumi in soils. Exianliumi inclined to bind more to Heilongjiang soil (HLJS), followed by Nanjing soil (NJS) and Jiangxi soil (JXS). Soil thin-layer chromatography and column leaching tests showed a weak migration in HLJS and strong mobility in JXS. Under the same condition, exianliumi rapidly decayed in NJS, followed by HLJS and JXS. The differential degradative capacity for exianliumi in the soils was related to chemical, physical and biological interactions basically through organic matter content, temperature, soil moisture and microorganisms. The half-normal, normal and pareto effect plots demonstrated that temperature, microorganisms and soil moisture dominantly influenced the degradation of exianliumi. We further characterized metabolites of exianliumi catabolized in NJS using High Resolution Liquid Chromatography-Quadrupole-Time of Flight-Mass Spectrometer/Mass Spectrometer (HRLC-Q-TOF-MS/MS). Eight degradation products and three conjugates of exianliumi were detected and the possible degradative pathways were highlighted. This is the first report about exianliumi degradation in soils with multi-pathways, which provides the basic data for environmental risk assessment of crop production and food security. Highlights: Physical adsorption of exianliumi in three representative types of agricultural soils. The mobility and adsorption of exianliumi in the soils were affected by TOC. Degradation of exianliumi in the soils was mainly by microorganisms. A degradation pathway for exianliumi in soil was proposed.